HUBUNGAN SIFAT DASAR DAN SIFAT PENGERINGAN LIMA JENIS KAYU ANDALAN JAWA BARAT - Efrida Basri; Nurwati Hadjib (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
This study was intended to investigate the relation between basic properties and drying properties of five priority wood species, i.e. pulai kongo (Alstonia congensis Engl.), kibawang (Azadirachta excelsa Jack.), salamander (Grevillea robusta A.Gunn), mahoni (Swietenia macrophy/la King), and suren (foona sureni Merr.)from West Java. The air drying methods used were 29 - 35°C temperatures and high temperature drying (JOrJ'C). The basic properties included basic density, shrinkage, modulus of rupture (MOR), compression parallel to grain (Cl/), wood strength and anatomical structures. The drying properties included drying duration and wood quality. The maximum-minimum temperature and humidityfor each species were based on defects resulted in high temperature drying.The results showed that the drying properties were significantly affected by basic density and wood anatomical structure. Following the drying qualities and basic properties, the optimal drying schedules for pulai kongo and mahoni wood at 70 - 95°C temperature and 29 - 75% humidity; kibawang wood at 65 - 88°C temperature and 29 - 78% humidity; suren wood at 65 - 9rJ'C temperature and 29 - 78% humidity; and salamander wood at 58 - 83°C temperature and 27 - 82% humidity. These drying schedules, however, still need further trial prior to their implementation in the factory-scale operation. Based on basic density, strength class, and decorative value, kibawang, salamander, mahoni and suren wood were suitable forfancy furniture.